Pola Pemberian MP-ASI Anak Usia 6-23 Bulan Berdasarkan Leaflet Kemenkes di Wilayah Kerja Puskesmas Kapasa - Destriyani, Destriyani; Nursalim; Ipa, Agustian (Universitas Sulawesi Barat, 2025)
The first 1,000 days of life represent a crucial period for a child's growth and development. Appropriate complementary feeding practices are key to fulfilling the nutritional needs of children aged 6–23 months. This study aimed to explore the complementary feeding patterns of children aged 6–23 months based on the Ministry of Health’s leaflet in the working area of Kapasa Public Health Center. This research employed a descriptive quantitative design using purposive sampling, involving 94 parents of children aged 6–23 months. Data were collected through questionnaires and the Ministry of Health leaflet, then analyzed descriptively using SPSS. Most respondents were housewives aged 20–35 years with low family income. The majority of children had normal nutritional status based on weight-for-age and height-for-age indicators. The findings showed that 72.4% of children met the minimum dietary diversity, 88.3% consumed eggs, fish, or meat (EFM), and 72.4% received appropriate complementary feeding. Dietary diversity and EFM consumption increased with the child’s age. Dietary diversity and the consumption of animal protein play a vital role in meeting children’s nutritional needs. Improvements in complementary feeding practices are still needed, particularly through parental education on food selection in accordance with balanced nutrition guidelines to support the optimal growth and development of children aged 6–23 months.